Techno-economic assessment of small-scale gas to liquid technology to reduce waste flare gas in a refinery plant. (February 2023) - Zayer Kabeh, Kaveh; Teimouri, Aidin; Changizian, Sina; Ahmadi, P.
Highlights: The central role of disseminated toxic gases in the atmosphere is undeniable. Small-scale gas to liquid technology (GTL) can be implemented to recover flare gas. Aspen HYSYS is used to model the different units of the small-scale GTL plant. Reliable data published by technology developers are used for technical simulation. The economic evaluation is performed by assessment of effective economic factors. Effective economic factors are used to perform sensitivity analysis. Abstract: The dissemination of toxic substances to the atmosphere and wasting energy by flaring are important challenges for natural gas facilities, and small-scale gas to liquid (GTL) technology can be used as an efficient method to reduce flaring. In this study, a validated model for technical simulation and variable sales prices of GTL products in five different scenarios are used to perform an accurate, comprehensive, and realistic techno-economic assessment of this technology to reduce flaring in the natural gas refinery. The detailed model of gas sweetening, syngas generation and Fischer-Tropsch synthesis (FTS) units have been simulated in the Aspen HYSYS software. The technical results illustrate that the capacity of this plant is 686 barrels per day, and the main products of this plant are diesel and propane. The results demonstrate the economic feasibility of a small-scale GTL plant in all economic conditions unless oil prices decrease significantly in the following years. Based on the obtained results, rising oil price increases the simulated plant's internal rate of return (IRR) to 39.99%. Finally, the sensitivity analysis results indicate that the profitability of this plant can be guaranteed with low oil prices by reducing CapEx to US$ 50, 000 per barrel.